Heroin overdose – suicide or accident? - Dragišić, Tatjana; Jovanović, Mirjana; Dickov, Aleksandra; Bugarski, Tamara; Ivetić, Olga; Mišković, Mirjana (Vojnosanitetski pregled, 2020)
Background/Aim. Suicide is a public health problem. Due to frequent overdose among drug addicts, there is a question about suicidality in this population. The aim of this study is to determine the specificity and distinctive factors in opiate addicts who have overdosed with an intention to commit suicide compared to addicts who have overdosed accidentally. Methods. The survey included 150 heroin addicts who were in the substitution program: 49 subjects who overdosed with a clear suicidal intention and 101 addicts who overdosed without suicidal intention. The subjects filled out the questionnaire about socio-demographic data and data regarding their addiction, the Minnesota Multiphasic Personality Inventory-2 (MMPI-2) as well as the Manchester Short Assessment of Quality of Life (MANSA) questionnaire about the quality of life. For statistical analysis, Pearson's χ2 test, Student t-test and univariate variance analysis were used. Results. The addicts who attempted suicide wеre younger persons (29.7 vs. 36.3 years of age), started to take heroin earlier (17.8 vs. 21.3 years of age; p= 0.013), they use it for a longer period (14.1 vs. 9.2 years; p = 0.00) and take it intravenously for a longer period (11.6 vs. 6.5 years; p = 0.00). The suicide was preceded by a traumatic event (p = 0.015) and there were several attempts of suicide (p = 0.004). The quality of life regarding accommodation, friends and organization of their free time was assessed as not so good (p = 0.03). Conclusion. In accordance with the obtained data, it is necessary to design programs for the prevention of suicide among addicts in general and especially programs that would be aimed at younger addicts.
Keywords: heroin dependence; opiate substitution treatment; drug overdose; suicide; risk factors.